2010
DOI: 10.1186/1471-2180-10-320
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal collagen-like surface protein 1 promotes adhesion to the respiratory epithelial cell

Abstract: BackgroundCollagen-like surface proteins Scl1 and Scl2 on Streptococcus pyogenes contain contiguous Gly-X-X triplet amino acid motifs, the characteristic structure of human collagen. Although the potential role of Scl1 in adhesion has been studied, the conclusions may be affected by the use of different S. pyogenes strains and their carriages of various adhesins. To explore the bona fide nature of Scl1 in adherence to human epithelial cells without the potential interference of other streptococcal surface fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The genes deleted in these strains may have functions in infection or biofilm formation that are redundant with other genetic determinants, such that their phenotypes are masked in the assays used here. This precise type of effect has been reported with streptococcal adhesins (50,51).…”
Section: Discussionmentioning
confidence: 82%
“…The genes deleted in these strains may have functions in infection or biofilm formation that are redundant with other genetic determinants, such that their phenotypes are masked in the assays used here. This precise type of effect has been reported with streptococcal adhesins (50,51).…”
Section: Discussionmentioning
confidence: 82%
“…S1 in the supplemental material). Furthermore, the role of Scl-1 in immune resistance is likely due to the N-terminal domain of M1 serotype Scl-1, as the collagen-like domain appears to chiefly play a role in bacterial adhesion to host cells (19,20). Sequence analysis of the N-terminal domain of M1 Scl-1 did not reveal significant homology to other proteins of known function (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Scl-1 is an LP(X)TG motif protein anchored to the GAS cell wall, and in studies utilizing recombinant protein, Scl-1 has been shown to interact with extracellular matrix proteins and host cells (15,(18)(19)(20). We first tested whether Scl-1 contributed to M1T1 GAS virulence using a mouse model of localized subcutaneous infection.…”
Section: Scl-1 Is Important For Bacterial Persistence In a Mouse Modementioning
confidence: 99%
See 1 more Smart Citation
“…Rgg bound to noncoding DNA upstream of genes encoding the antiphagocytic M protein (20,21,56), SOF (57), SfbX49 (30), and streptococcal collagen-like surface protein B (SclB) (19). Each gene product is localized to the cell surface and covalently attached to peptidoglycan, and each is thought to contribute to virulence (19,20,21,29,47,57). Previous analyses showed that Rgg represses the expression of each of the genes (26), suggesting that the protein directly represses their expression.…”
Section: Identification Of Rgg Binding Sites In Vivomentioning
confidence: 99%